Severe Raynaud in a young female with Mixed Connective Tissue Disorder (MCTD) - Thivacaren, S.; Ushagowry, S. (Jaffna Medical Association, 2022)
Raynaud phenomenon is clinically manifested by sharply demarcated colour changes of the skin of the digits due to abnormal vasoconstriction of digital arteries and cutaneous arterioles. Raynaud can be primary or secondary. Here we present a young female patient who presented with Raynaud, inflammatory type of small joint pain and proximal muscle weakness. She was diagnosed to have mixed connective tissue disease after extensive evaluation.
Keywords: Raynaud phenomenon; Mixed connective tissue disease; Autoimmune rheumatic disease